Cheiro-Oral syndrome caused by thalamus hemorrhage: A case report. Issue 2 (January 2018) - Wu, Yen-Hung; Liu, Kuan-Ting; Yeh, I-Jeng; Chang, Chia-Wen
Abstract: Rationale: Cheiro-Oral syndrome (COS) is a pure sensory deficit confined to the perioral area and ipsilateral distal fingers or hand. Owing to relatively minor clinical findings and various presentations in different cases, the insidious and severe illness it implies may be overlooked at acute settings. Patient concerns: A 70-year-old man with history of hypertension and type II diabetes mellitus under regular medication control came to our emergency department with chief complaint of sudden onset of right perioral region and right upper limb numbness. General physical and neurological examinations were normal except for subtle hypoesthesia to light touch, and pinprick in the right corner of mouth and right forearm to distal fingers. Diagnoses: Routine blood analysis was all in normal range including white blood cell count, hemocrit platelet, renal and liver function, and electrolytes such as sodium and potassium. Noncontrast brain computed tomography showed abnormal high-attenuation collection in the left thalamus. Intervention: Follow-up computed tomography showed absorption of the hemorrhage after strict control of his blood pressure. Outcomes: The patient was discharged 7 days later from our hospital with stable condition. Lessons: We demonstrated type I COS associated with thalamic hemorrhage to highlight the neurological implication of COS. It is crucial for emergency clinicians to recognize the symptoms and promptly order a neuroimaging study to exclude large infarction/hemorrhage, which would deeply affect the disposition and following treatment of the patient.